2021
DOI: 10.1007/s00018-021-03881-z
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic signaling by cells of the immune system: more the rule than the exception

Abstract: Gamma-aminobutyric acid (GABA) is best known as an essential neurotransmitter in the evolved central nervous system (CNS) of vertebrates. However, GABA antedates the development of the CNS as a bioactive molecule in metabolism and stress-coupled responses of prokaryotes, invertebrates and plants. Here, we focus on the emerging findings of GABA signaling in the mammalian immune system. Recent reports show that mononuclear phagocytes and lymphocytes, for instance dendritic cells, microglia, T cells and NK cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 134 publications
(200 reference statements)
4
41
0
Order By: Relevance
“…1e ). Consistent with the previous findings on the GABA-R expression profile in immune cells 14 . T eff cells express a selected group of GABA-R subunits.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1e ). Consistent with the previous findings on the GABA-R expression profile in immune cells 14 . T eff cells express a selected group of GABA-R subunits.…”
Section: Resultssupporting
confidence: 93%
“…In line with earlier studies 14 , we have found that Teff cells express various subunits of GABAA receptor (GABAA-R) (Fig. 1f).…”
Section: Gab Can Serve As An Autocrine Signaling Metabolite That Regu...supporting
confidence: 92%
See 2 more Smart Citations
“…Mammalian and fish skin share protective activities against environments that are rich in infectious agents. Fish epidermis is endowed with an extrinsic barrier consisting of a mucus layer and antimicrobial peptides [92]. Recent findings point to the mechanisms through which pathogens interact with each other on the skin and the signaling systems that mediate the communication between the immune system and skin-associated pathogens.…”
Section: Neuro Mast Cell Crosstalk In the Skinmentioning
confidence: 99%